Minor head trauma - assessment, management, and rehabilitation - Mandel, Steven; Sataloff, Robert Thayer (Springer, 1993)
Minor Head Trauma describes and explains techniques for diagnosing, evaluating, and rehabilitating patients with minor head injuries. This book emphasizes the importance of long-term treatment of patients beyond the initial moments of injury and treatment in the emergency room. Minor Head Trauma offers insight on: - a range of related issues from emergency room management to psychiatric evaluation and rehabilitation; - the role of electrophysiological testing in patients - including BEAM techniques; - the subtleties of neurophysiological diagnosis; - neurotoxicological evaluation and treatment; - diagnosis and treatment of temporomandibular joint disorders; - the nature and pathogenesis of visual sequelae of head injury; - the speech-language pathologist\'s role in treating minor head injuries; - the complexities of rehabilitation including problems faced when the patient resumes normal community, professional and familial activities. Minor Head Trauma is intended for physicians, psychologists, physical therapists, speech-language pathologists, nurses, attorneys, and others faced with the challenges of evaluating and treating patients who have sustained minor head trauma.
Keywords: neurochirurgie; traumatologie; mozek - poškození - komplikace - příručky; mozek - poškození - nemocní - rehabilitace - příručky; neurologie